Treatment of Kawasaki Disease: A Network Meta-Analysis of Four Dosage Regimens of Aspirin Combined With Recommended Intravenous Immunoglobulin - Huang, Ying-Hua; Hsin, Yi-Chen; Wang, Liang-Jen; Feng, Wei-Ling; Guo, Mindy Ming-Huey; Chang, Ling-Sai; Tu, Yu-Kang; Kuo, Ho-Chang (Frontiers in Pharmacology, 2021)
Aspirin was once believed to reduce the mortality of Kawasaki disease (KD) due to its effect on the thrombotic occlusion of coronary arteries. However, conflicting evidence has been found regarding aspirin treatment and its benefit in patients with acute KD. We compared the efficacy of different aspirin doses in acute KD. A literature search of PubMed, EMBASE, and Cochrane databases was conducted to identify studies comparing different doses of aspirin for acute KD. The primary outcome of interest was coronary artery lesions (CAL). We used random-effects network meta-analysis. Six retrospective studies, including 1944 patients receiving aspirin in doses of 0, 3-5, 30-50, or 80-100 mg/kg/day, were selected. The risks of CAL were not significantly different for the various doses of aspirin compared to the placebo: odds ratio (OR) was 1.10 (95% confidence interval [CI]: 0.70–1.71) for patients with aspirin 3-5 mg/kg/day; OR = 1.23 (95% CI: 0.67–2.26) for aspirin 30-50 mg/kg/day, and OR = 1.59 (95% CI: 0.74, 3.421) for 80-100 mg/kg/day. The P-score ranged from 0.76 for placebo to 0.19 for aspirin 80-100 mg/kg/day. The different doses of aspirin exhibited no significant difference with regard to the efficacy of CAL or with the secondary outcomes of intravenous immunoglobulin resistance or hospital stays for acute KD. Therefore, we found that treatment without any aspirin is not inferior to other doses of aspirin and can also slightly reduce the risk of CAL.